L’ubica UČNIK and Anita WILLIAMS (eds.). Phenomenology and the Problem of Meaning in Human Life and History. Nordhausen: Traugott Bautz, 2017, 345 pp. - Bueno Junquero, Adrián (Investigaciones Fenomenológicas, 2021)
-